KANUNISASI HUKUM ISLAM DI INDONESIA (Perspektif Usul al-Fiqh) - Afandi, Mohammad (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
There is a lot of controversy about the canonization of the Islamic law in Indonesia which invites many of the muslim scholars, especially those who obtain education in formal institutions and those who receive it in traditional ones. Thanks to this long debate, the discourse of the canonization not only becomes a sensitive national issue but also has a practical effect all of the Indonesian muslim people feel, that is, there are some of Islamic acts such as the act of the marriage and the act of the heritage which are adopted as parts of the state law like KHI and number 41 of 2004‟s act about waqaf. Henceforth this discourse of canonization spreads more and more broadly, so that the syari‟a-based economic system is regarded as one of the definitive and effective solutions to overcome the economic crisis.Using the Islamic jurisprudence as an approach, this research tends to find out and set a pattern of the development of future formulation of Islamic law in Indonesia by posing an academic question as to in what fields the canonization can be done. As the result, we can organize Islamic laws or norms around three themes: (1) norms that in practice are under individual‟s authority; (2) norms that in practice are under people‟s authority; (3) norms that in practice are under state‟s authority. Only in the last norm, including the family law, the civil law, the law of politic,the law of judgment, and the criminal law, can the canonization of the Islamic law be done.